Teaching the rural poor about banking - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Linking self-help groups and banks in developing countries by E Kropp, Michael Marx, Ballurkar Pramod, Benjamin Quinones and Hans Dieter Seibel, 155pp 1989 GTZ/APRACA ISBN 3 88085 418 1 APRACA, Maliwan Mansions, Phra Atit Road, Bangkok 10200, THAI